PEMBINAAN DAN PENATAAN PEDAGANG KAKI LIMA - Harapan Tua R.F.S, Hari Indrawan, Achmad Hidir, (Jurnal Ilmu Administrasi Negara, 2020)
Competence, Work Environment and Service Quality. This research is motivated by street vendors who are around the traditional market of Pekanbaru Government without permission and the location is in a zone that is forbidden to sell. This study uses a qualitative descriptive research method approach. The data is obtained directly through interviews with informants, namely the head of the section on Order, Hygiene and Guidance for street vendors, street vendors, and the community. The results of this study indicate that, the program carried out in the guidance and structuring of street vendors, namely, direction and counseling, arrangement and market development. The implementation of PERDA No. 11 of 2001 concerning the guidance and arrangement of street vendors through these programs has not run optimally. Minimal and unsustainable coaching programs and market development that are not well considered so that a market has been built but is neglected because it is no longer used. There are several factors that become obstacles in the guidance and structuring of street vendors in Pekanbaru, namely, human resources, facilities and budgets that are not met, lack of supervision, economic factors, education, weak public awareness of rules, and urbanization factors.